Economic capital what it is and what every bank manager should know - Klaassen, Pieter
Economic Capital: How It Works and What Every Manager Needs to Know clarifies how economic capital can be defined, measured, and implemented in a manner that adds value to an organization. It does so in a way that is accessible to a broad audience, including senior managers of financial institutions, supervisors, analysts, and risk modelers. The book illustrates main concepts and choices with many examples and actual events in financial markets, including those in the recent sub-prime crisis. The authors also discuss the role of economic capital within the broader context of management responsibilities and activities, and its relation to other risk management tools that are available to the modern risk manager. Takes a managerial view on economic capital in relation to capital adequacy, risk management, and performance management, which aids management understanding of how risk modelling and economic capital can help to control risk and balance risk and return. Presents real dilemmas and discusses possible solutions when setting up an economic capital framework in an institution, which helps managers to make informed choices for a consistent and effective risk and performance framework within their institution. The Non-mathematical and intuitive discussion of topics that are otherwise the exclusive domain of mathematicians creates a book that is accessible to a broad audience in financial sector, from managers and supervisors who want to understand and control the risk models that financial institutions use, to analysts and modelers. Structured and complete discussion of all relevant aspects of economic capital, from purpose and definition to measurement, implementation, and use can be utilized as a source of reference for discussions between managers, supervisors and modelers. Illustrations with many actual events from the sub-prime and other financial crisis explain what risks caused these crises and how risk models and managers can identify these risks and reflect them in an economic capital framework. Contains description of risk modelling approaches for a large number of risks, which enables consistent risk modelling for large number of risks within an economic capital framework.